Maternal determinants of average weekly fetal weight gain in Yogyakarta, Indonesia - Eugenius Phyowai Ganap; Pakartian Ayu Sugmana; Riantina Rizky Amalia; Laksmi Ika Hidayati; Aditya Doni Pradana Doni Pradana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Average fetal weight gain (AWG) is one of the important parameters usuallyused as an indicator to identify the fetal risk of poor outcomes of intrauterinegrowth restriction (IUGR) or macrosomia. This study aimed to investigate theassociation between AWG and maternal factors such as body weight (BW), bodymass index (BMI), middle-upper arm circumference (MUAC), and economicstatus in Yogyakarta, Indonesia. This community-based cross-sectional studywas conducted in one district in the Yogyakarta Special Province, Indonesia.The study included 50 mother-infant pairs who delivered at term (37-42 weeksof pregnancy). The mother’s BW, height, BMI, and MUAC were recorded usinga case-report form. Questionnaires were also completed to establish therespondents’ economic status. Maternal factors associated with fetal birthweight were determined using univariate and multivariate analyses. Themothers registered in our study mostly had good nutritional status (74.0% hadan optimal MUAC > 23cm). The mean AWG and birth weights were 172.6 ±24.5g/wk and 3.08 ± 0.34kg, respectively. Univariable analysis models wereused to assess the associations between each variable and AWG (with a cut-offvalue of 153.8 g/wk). Our study found no associations between higher MUACand higher AWG (OR=1.03; 95% CI: 0.83-1.27; p=0.77) and energy intakes perday with AWG (OR=1.0; 95% CI: 1.00-1.001; p=0.21). Socioeconomic factors suchas the mother’s educational background also showed no association with AWG(OR=0.38; 95% CI: 0.92-1.57; p=0.18). In conclusion, this finding shows that thereis no association between variables such as MUAC, mother’s age, energy intake,and educational background with the average fetal weight gain achieved.